Auditory processing in people with chronic aphasia - Pavičić Dokoza, Katarina (Array, 2020)
The preconditions for successful voice communication are good hearing and listening, and auditory processing that includes the ability to process the audio signal. Damage or deceleration of sound signal processing at any level from the periphery to the central structures leads to disintegration and inability to process the signal effectively. Auditory processing in people with aphasia has not been examined in Croatia to date. Results of studies conducted in other languages point to negative effects of auditory processing difficulties on the receptive and expressive component of the language. This study was conducted on a sample of subjects with chronic aphasia and a group of control subjects with no neurological or any other disorders that can affect auditory processing. The inclusion criteria for persons with aphasia were impaired language skills as a result of cerebrovascular accident that occurred at least six months before the examination, regardless of severity and type of aphasia and normal hearing status. The study did not include persons with aphasia who were unable to repeat the six-word sentence, due to impaired comprehension or speech expression, and those whose comprehension was not sufficient to cooperate well during the test. The test was conducted individually for 30 minutes per subject using the Auditory processing test (PSP) that is standardized for the Croatian language. Results from this study showed statistically significant lower achievement on all subtests on PSP-1 (filtered words, speech in noise, dichotic words test, and dichotic sentence test) in people with aphasia compared with the control group. People with aphasia and control group subjects showed better results in favor of the left ear on variable speech in noise. Filtered words were easily processed through the left ear in people with aphasia while dichotic sentences were easily processed through the left ear in the control group.